2019
DOI: 10.12688/wellcomeopenres.15469.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing participation in controlled human infection models: a pooled analysis from six enteric fever studies

Abstract: Background: Enteric fever is an acute febrile-illness caused by infection with the human-restricted Salmonella serovars Typhi and Paratyphi. Controlled human infection models (CHIM) of S. Typhi and Paratyphi infection are used to accelerate vaccine development and to better understand host-pathogen interactions. The primary motivations for participants to take part in these studies are unknown. We studied participant motivations, attitudes and the factors influencing CHIM study participation. Methods: Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…53 Similarly, studies looking at motivations of CHIM participants in the UK, which still experience infectious diseases although at lower rates than LMICs, found that the 'desire to contribute to the progression of medicine' was the biggest motivator for CHIM participation, even above monetary compensation. 54 The COVID-19 pandemic has been a cruel reminder that infectious diseases can cause immense economic, social and health impacts from which no country is immune. Hence, it would be reasonable to assume that many, if not all, of those signing up to partake in the COVID-19 CHIM are strongly motivated to find a vaccine that will save lives and allow society to go back to normal, over and above any financial compensation they will receive.…”
Section: Ethical Analysismentioning
confidence: 99%
“…53 Similarly, studies looking at motivations of CHIM participants in the UK, which still experience infectious diseases although at lower rates than LMICs, found that the 'desire to contribute to the progression of medicine' was the biggest motivator for CHIM participation, even above monetary compensation. 54 The COVID-19 pandemic has been a cruel reminder that infectious diseases can cause immense economic, social and health impacts from which no country is immune. Hence, it would be reasonable to assume that many, if not all, of those signing up to partake in the COVID-19 CHIM are strongly motivated to find a vaccine that will save lives and allow society to go back to normal, over and above any financial compensation they will receive.…”
Section: Ethical Analysismentioning
confidence: 99%
“…Importantly, even when healthy participants are motivated by money, available data indicate that perceived risk is their ultimate deciding factor, and they will avoid studies they perceive to be too risky. These findings about motivation and decision-making among healthy participants in general are largely replicated in studies specific to HICS (Njue et al 2018;Kraft et al 2019;Oguti et al 2019;Jao et al 2020). HICS participants report that they engage in substantial deliberation before deciding to enroll, are not worried about study risks (perhaps unsurprisingly, given low risk of serious long-term harm in traditional HICS involving treatable diseases), and would consider participating again.…”
Section: Susceptibility To Financial Influencementioning
confidence: 80%
“…Another consideration when setting payment offers may be the stigma that sometimes accompanies HICS participation. Some HICS participants, for instance, report experiencing negative responses from family and friends or keeping their participation secret due to concerns about how it may be perceived (Roth 2007;Njue et al 2018;Kraft et al 2019;Oguti et al 2019;Hoogerwerf, de Vries, and Roestenberg 2020;Jao et al 2020). Even if the stigma is associated with perceived mercenary risktaking for money, however, that would be insufficient reason to reduce fair payment; the same is true to the extent that paying HICS participants might negatively influence public trust in this type of research.…”
Section: Stigmamentioning
confidence: 99%
“…Euzebiusz Jamrozik , 1,2,3 Michael J Selgelid 1 Human infection challenge studies (HCSs) provide illuminating case studies for several ongoing debates in research ethics, including those related to research risks and payment of participants. Grimwade et al 1 add to previous public engagement, qualitative evidence and philosophical literature on these topics.…”
Section: Should Practice and Policy Be Revised To Allow For Risk-propmentioning
confidence: 99%
“…Grimwade et al 1 add to previous public engagement, qualitative evidence and philosophical literature on these topics. [1][2][3][4][5][6][7][8] The authors advocate revision of research payment policy and practice based on their main finding that members of the public endorse ex ante payment of participants proportional to research-related risk exposure, in addition to post hoc compensation for any lasting harms that occur. 1 Although 'payment for risk' would diverge from most current research ethics guidelines, it is noteworthy that the difference in payment to participants that their framework would allow might only be small, at least in the case of currently accepted studies.…”
Section: Should Practice and Policy Be Revised To Allow For Risk-propmentioning
confidence: 99%